On-paper electrophoresis for protein separation - Lai, Samantha Yu Shan (2014)
Research on paper-based microfluidics has been increasing rapidly in recent years. Many of these devices are used as low-cost alternatives for fast diagnostics and biochemical analysis. Electric fields have been popular for microfluidics separations. Due to the large surface to volume ratios, joule heating can be dissipated rapidly, allowing for the application of high potential voltage and thus efficient separation of amino acids, DNA molecules, proteins and peptides. This project explores electrophoresis on paper-based microfluidics for analytical capabilities and application in separation and electrokinetic investigation of proteins and nucleic acids. Photolithography technique was used to fabricate microchannels to form the paper-based microfluidics chip and filter paper is placed into an apparatus for electrophoresis. Proteins and DNA displayed migration of molecules and demonstrated functionality of incorporating Paper-base microfluidics and electrophoresis for Protein and DNA separation base on their charges.